(untitled) (Orfeu, 2025)
Based on the observation that music in the classroom should receive greater attention within the Art discipline, the methodology of collective recorder teaching is proposed, seeking to show its importance in the musicalization of elementary school children. starting from a review of the history of recorder teaching in Brazil, and its inherent pedagogical aspects. In addition, autobiographical narrative research and the development of an educational product were included that aims to assist teachers in the musicalization of students in the 5th year of Elementary School I. The proposal uses the recorder as an alternative to the inclusion of a musical instrument in the public-school network. In this context, the instrument used proves to be a resource to be appropriate, not the only one, but important in the musicalization of elementary school. Being a low-cost and easy-to-learn instrument, the flute is widely used in the early years. Thus, based on this methodology, the educational product developed consists of a didactic sequence that aims to assist music educators in using the recorder in elementary school.